Von Willebrand Disease: A Database of Point Mutations, Insertions, and Deletions - Ginsburg, David; Sadler, Evan J (Thrombosis and Haemostasis, 1993)
The current system for the diagnosis and classification of von Willebrand disease (vWD) is quite complex, with more than 20 distinct variants described. Over the past few years considerable progress has been made toward an understanding of vWD at the molecular level. A small cluster of mutations within the vWF A1 homologous repeat appears responsible for over 90% of type IIB vWD. A similar cluster of mutations in the vWF A2 homologous repeat accounts for the majority of type II A vWD. By RFLP analysis, several type II vWD mutations have been shown to be recurrent on distinct haplotype backgrounds, suggesting independent genetic origins (see accompanying manuscript for a complete list of known polymorphisms). Several mutations at the N-terminus of the mature vWF subunit have been identified in association with abnormal factor VIII binding. Homozygotes for this abnormal vWF present with a hemophilia-like phenotype that is autosomal recessive in inheritance. In a small subset of patients with type III vWD large gene deletions have been identified on one or both vWF alleles. Carriers heterozygous for a deleted locus and one normal vWF gene are generally asymptomatic. Nonsense mutations and other defects resulting in loss of vWF mRNA expression from one allele have also been associated with a recessive type III vWD phenotype. No distinct molecular defect responsible for classic type I vWD has yet been defined.